Ultrasound and gross anatomy of the brachial plexus and major nerves of the forelimb. An anesthetic approach using the domestic rabbit (Oyctolagus cuniculus) as an experimental model1 - Mencalha,Rodrigo (2016)
PURPOSE: To update the gross and sonographic anatomy and propose landmarks to perform ultrasound-guided (US-guided) axillary brachial plexus block (BPB) in rabbits. METHODS: Forty New Zeeland's rabbit (NZR) cadavers were dissected and the nerves were trimmed, identified, measured, and photographed. Additionally, in twenty NZRs, sonographic images of brachial plexus (BP) were performed through a simple-resolution ultrasound device. The US-guided block was achieved through a minimum volume of lidocaine necessary to surround the BP roots. The effectiveness of the brachial plexus block was assessed on sensitivity and motor functions. RESULTS: The BP resulted from connections between the ventral branches of the last four cervical spinal nerves and the first thoracic spinal nerve. In the axillary sonoanatomy, the BP appeared as an agglomerate of small, round hypoechoic structures surrounded by a thin hyperechoic ring. The amount of time and the minimum volume required to perform was 4.3 ± 2.3 min and 0.8 ± 0.3ml, respectively. CONCLUSIONS: The gross and sonographic anatomy of the BP showed uncommon morphological variations. Moreover, from sonographic landmarks, we showed complete reproducibility of the axillary US-guided brachial plexus block with simple resolution equipment and small volume of anesthetics required.